Porous inorganic particles, and composite fillers, products using the same
Patent Information
- Application Number
- CN202380011204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-03-06
AI Technical Summary
[0009]然而,应用于常规使用的羧甲基纤维素和钙颗粒的复合填充物的钙颗粒为具有光滑表面的球形高密度固体颗粒,其具有生物活性低的局限性
[0118] According to this disclosure, porous inorganic particles with high production efficiency and excellent bioactivity and strength can be provided, as well as composite fillers and products using them.
Smart Images

Figure CN117202945B_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0036793, filed on March 24, 2022, with the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety.
[0003] This disclosure relates to porous inorganic particles, as well as composite fillers and products using the same. Background Technology
[0004] Fillers are supplementary materials or contents injected or embedded in wrinkles or indented scars, and are widely used for human organs that need to maintain volume, such as wrinkles, scars, cosmetic surgery, or vocal cords.
[0005] Fillers are classified as permanent, semi-permanent, and temporary based on the length of time they remain in the tissue, and specific examples include collagen, fat, hyaluronic acid, hydroxyapatite, polymethyl methacrylate, botulinum toxin, etc.
[0006] While conventionally used hyaluronic acid fillers can provide a fuller appearance to the treated area, their drawbacks include the inability to fundamentally improve skin elasticity, rapid degradation, and short-lived effects.
[0007] In addition, calcium fillers not only promote the production of natural collagen and have a fundamental skin improvement effect, but also have the advantages of slow decomposition rate and long duration of effect. However, they have the disadvantages of low bioactivity and slow skin improvement effect.
[0008] To overcome the limitations of such single-component fillers, a method using composite fillers—a mixture of biocompatible polymers (e.g., carboxymethyl cellulose) and calcium particles—has been proposed. These composite fillers overcome the limitations of single-component fillers, maintain their initial volume, and then stimulate the production of natural collagen through the tissue stimulation of the calcium particles, thereby exhibiting an effect that improves the skin itself.
[0009] However, the calcium particles in the commonly used carboxymethyl cellulose and calcium particle composite fillers are spherical, high-density solid particles with smooth surfaces, which have limitations due to their low bioactivity. Furthermore, the low biodegradability of carboxymethyl cellulose presents challenges during orthodontic treatment.
[0010] Therefore, there is a need to develop fillers that have improved bioactivity compared to existing calcium particles, rapidly demonstrate skin improvement effects, and are able to maintain initial volume and the correction process. Summary of the Invention
[0011] Technical issues
[0012] One objective of this disclosure is to provide porous inorganic particles with high production efficiency, as well as excellent bioactivity and strength.
[0013] Another objective of this disclosure is to provide a composite filler in which porous inorganic particles produced by a highly efficient method are introduced into the composite filler to enhance the bioactivity of the composite filler and improve skin improvement, thereby exhibiting high biodegradability and enabling corrective processes.
[0014] Another objective of this disclosure is to provide products using composite fillers with improved bioactivity.
[0015] Technical solution
[0016] To achieve the above objectives, this paper provides porous inorganic particles comprising a sintered body of calcium-based particles and a core-shell structure with pores distributed in the sintered body and having a core with high porosity and a shell with lower porosity than the core. The calcium-based particles include a first calcium-based particle with a maximum diameter of 10 nm to 500 nm and a second calcium-based particle with a maximum diameter of 1 μm to 10 μm.
[0017] This article also provides composite fillers comprising porous inorganic particles and biodegradable carriers.
[0018] This document further provides products containing the aforementioned composite filler.
[0019] The porous inorganic particles, composite fillers using the same, and products according to specific embodiments of this disclosure will be described in more detail below.
[0020] Unless otherwise stated throughout this specification, the technical terms used herein are for reference only to specific embodiments and are not intended to limit the scope of this disclosure.
[0021] Unless the context clearly specifies otherwise, the singular forms “a” and “the” used herein include plural references.
[0022] The terms “comprising” or “including” as used herein specify a particular feature, region, integer, step, action, element, and / or component, but do not exclude the presence or addition of different particular features, regions, integers, steps, actions, elements, components, and / or groups.
[0023] Ordinal terms such as "first" and "second" are used only for the purpose of distinguishing one component from another and are not limited by ordinal numbers. For example, without departing from the scope of the invention, a first component may be referred to as a second component, or similarly, a second component may be referred to as a first component.
[0024] The contents of this disclosure will now be described in more detail.
[0025] 1. Porous inorganic particles
[0026] According to one embodiment of this disclosure, porous inorganic particles can be provided, the porous inorganic particles comprising a sintered body of calcium-based particles and a core-shell structure having pores distributed in the sintered body and having a core with high porosity and a shell with lower porosity than the core, wherein the calcium-based particles include a first calcium-based particle with a maximum diameter of 10 nm to 500 nm and a second calcium-based particle with a maximum diameter of 1 μm to 10 μm.
[0027] The inventors have discovered that a porous inorganic particle of one embodiment not only has a higher porosity and specific surface area than existing high-density solid particles, thus improving bioactivity to rapidly induce the therapeutic effect of fillers, but also has a fast particle production rate, does not require further drying steps to achieve high productivity, does not use organic solvents and is therefore produced by a safe spray drying method without the risk of explosion, thereby maximizing production efficiency.
[0028] In particular, since porous inorganic particles include two types of calcium-based particles distinguished by their maximum diameter, they can have core-shell structures with different porosities within the particles, thereby ensuring sufficient porosity to enhance bioactivity and simultaneously improve the strength of the particles themselves.
[0029] Specifically, when all particles have uniform porosity, the strength of the particles weakens because the porous structure is even introduced to the outermost part of the particles. However, one embodiment of porous inorganic particles has a structure in which the core near the center of the particle has high porosity, while the outer shell of the particle, which is farther from the center of the particle, has lower porosity than the core. This can improve the strength of the particles.
[0030] One embodiment of porous inorganic particles may include a sintered body of calcium-based particles. Calcium-based particles refer to particles containing calcium, and may consist solely of calcium or be a mixture of calcium and other elements.
[0031] More specifically, calcium-based particles can include hydroxyapatite. Hydroxyapatite is a calcium phosphate component that forms the inorganic material of human teeth and bones, exhibits high biostability, and promotes the production of natural collagen, which has a fundamental wrinkle-reducing effect.
[0032] Calcium-based particles can include a first calcium-based particle and a second calcium-based particle. The first calcium-based particle has the following maximum diameters: 10 nm to 500 nm, or 10 nm to 400 nm, or 10 nm to 300 nm, 10 nm to 250 nm, or 100 nm to 500 nm, or 100 nm to 400 nm, or 100 nm to 300 nm, 100 nm to 250 nm, or 150 nm to 500 nm, or 150 nm to 400 nm, or 150 nm to 300 nm, or 150 nm to 250 nm. The second calcium-based particle has the following maximum diameters: 1 μm to 10 μm, or 1 μm to 5 μm, or 1 μm to 3 μm, or 2 μm to 10 μm, or 2 μm to 5 μm, or 2 μm to 3 μm. That is, calcium-based particles can simultaneously include two types of particles distinguished by their maximum diameters.
[0033] The diameter of a calcium-based particle is defined as the distance between two points where a straight line passing through the particle's centroid intersects the particle's outermost boundary line, with the maximum value of such a diameter corresponding to the maximum diameter. There are no particular limitations on the specific methods used to measure the maximum diameter of calcium-based particles, but it can be confirmed, for example, by using TEM or SEM images.
[0034] Since calcium-based particles comprise two types of particles distinguished in this way by their maximum particle diameter, they can have core-shell structures with different porosities within the particles, thereby ensuring sufficient porosity to enhance bioactivity and also improving the strength of the particles themselves.
[0035] There are no particular limitations on the shape of calcium-based particles, and various shapes of conventionally known hydroxyapatite can be used without restriction. Examples of shapes for calcium-based particles include spherical, rod-shaped, needle-shaped, linear, plate-shaped, and flake-shaped particles. There are no particular limitations on the specific methods used to measure the shape of calcium-based particles, but these can be confirmed, for example, by TEM or SEM images.
[0036] However, for example, the first and second calcium-based particles can be spherical. When the first calcium-based particle, with a maximum diameter of 10 nm to 500 nm, is spherical, porous inorganic particles can be produced in a spherical shape during production using a spray drying method.
[0037] Furthermore, when the shape of the second calcium-based particle, with a maximum diameter of 1 μm to 10 μm, is not spherical, the surface roughness of the second calcium-based particle increases, which may lead to the need for high injection force when injected into the body.
[0038] The content of the second calcium-based particles may be 2 to 10 parts by weight, or 2 to 5 parts by weight, or 3 to 10 parts by weight, or 3 to 5 parts by weight, relative to 1 part by weight of the first calcium-based particles.
[0039] When the content of the second calcium-based particles is excessively reduced to less than 2 parts by weight relative to 1 part by weight of the first calcium-based particles, there is a limitation on insufficient formation of the nucleus of the second calcium-based particles. This makes it difficult to ensure a high specific surface area of the porous inorganic particle nucleus and therefore may not be possible to produce porous inorganic particles in a spherical shape.
[0040] Meanwhile, when the content of the second calcium-based particles is excessively increased to more than 10 parts by weight relative to 1 part by weight of the first calcium-based particles, there is excessive restriction on the formation of pores in the second calcium-based particles, and therefore the formation of the shell of the first calcium-based particles becomes insufficient and the particle strength weakens.
[0041] Calcium-based particle sintered bodies refer to products obtained by subjecting aggregates of multiple calcium-based particles to a high-temperature sintering process. Sintering refers to the phenomenon where powder, as an aggregate of multiple particles, melts, adheres to each other, and solidifies when heated to a temperature equal to or below its melting point. In other words, porous inorganic particles correspond to secondary particles obtained by sintering calcium-based powder containing a large number of primary calcium-based particles.
[0042] Simultaneously, porous inorganic particles may include pores distributed within the sintered body. Since the pores are distributed within the calcium-based particle sintered body, the porous inorganic particles can exhibit porosity. More specifically, the pores may be distributed within and / or on the surface of the calcium-based particle sintered body.
[0043] The term "pore" refers to the empty space inside the sintered body of calcium-based particles, and can also refer to holes, depressions, cavities, voids, etc. As used herein, the term "porous particle" can refer to a particle having pores inside and / or on its surface.
[0044] When porous inorganic particles include pores distributed in the sintered body, the bioactivity of the sintered body is improved due to the increased surface area caused by the pores, and it can quickly show a high skin improvement effect.
[0045] As will be described later, pores can originate from the sintering process of calcium-based particles. Specifically, pores correspond to spaces formed between calcium-based particles by adjusting sintering conditions during sintering.
[0046] At this point, porous inorganic particles can have a core-shell structure with a core having high porosity and a shell having lower porosity than the core. Based on the radius of the distance from the centroid of the porous inorganic particle to its outermost boundary line, the region within 90%, 80%, 70%, 60%, or 50% of the radial diameter starting from the centroid of the porous inorganic particle can be defined as the core. Furthermore, the remaining region outside the core can be defined as the shell.
[0047] Specifically, the core thickness of porous inorganic particles can be 10 μm to 45 μm, or 10 μm to 42 μm, or 10 μm to 40 μm, or 10 μm to 22 μm, or 10 μm to 20 μm. The core thickness of a porous inorganic particle refers to the distance between two points where a straight line passing through the centroid of the particle intersects the outermost surface of the core. The core thickness of porous inorganic particles can be obtained using SEM. When the core thickness of porous inorganic particles is not constant, the arithmetic mean of the maximum and minimum thickness values can be calculated as the core layer thickness.
[0048] When the core thickness falls within the aforementioned range, porous inorganic particles can adequately ensure the porosity of the core. However, when the core thickness is excessively reduced, it becomes difficult to ensure sufficient porosity.
[0049] Specifically, the core diameter of porous inorganic particles can be 20 μm to 90 μm, or 20 μm to 84 μm, or 20 μm to 80 μm, or 20 μm to 44 μm, or 20 μm to 40 μm. The core diameter of a porous inorganic particle refers to the distance between two points where a straight line passing through the centroid of the core inside the particle intersects the outermost boundary line of the core, where the maximum value of such a diameter corresponds to the maximum diameter. There are no particular limitations on the specific methods used to measure the core diameter of porous inorganic particles, but it can be confirmed, for example, by using SEM images. The core diameter of the porous inorganic particle corresponds to approximately twice the aforementioned core thickness.
[0050] When the core diameter falls within the aforementioned range, porous inorganic particles can adequately ensure porosity through the core. If the core diameter decreases excessively, it becomes difficult to ensure porosity.
[0051] The shell thickness of porous inorganic particles can range from 0.1 μm to 25 μm, or 0.1 μm to 20 μm, or 0.1 μm to 15 μm, or 0.1 μm to 10 μm, or 1 μm to 25 μm, or 1 μm to 20 μm, or 1 μm to 15 μm, or 1 μm to 10 μm, or 2 μm to 25 μm, or 2 μm to 20 μm, or 2 μm to 15 μm, or 2 μm to 10 μm. The shell thickness of porous inorganic particles is defined as the difference (L1-L2) obtained by subtracting the core thickness (L2) from the distance (L1) from the distance from the center of gravity of the porous inorganic particle to the point where a straight line passing through the center of gravity intersects the outermost surface of the shell. The shell thickness of porous inorganic particles can be obtained using SEM. When the shell thickness of porous inorganic particles is not constant, the arithmetic mean of the maximum and minimum thickness values can be calculated as the shell thickness.
[0052] When the shell thickness falls within the aforementioned range, porous inorganic particles can sufficiently ensure strength through the shell. When the shell thickness is excessively reduced, it becomes difficult to ensure strength.
[0053] Porous inorganic particles can have a core diameter of 20 μm to 90 μm and a shell thickness of 0.2 μm to 50 μm. More specifically, the ratio of core diameter to shell thickness (core diameter: shell thickness) of porous inorganic particles is 1:1 to 100:1, or 2:1 to 100:1, or 5:1 to 100:1, or 7:1 to 100:1. Within this range, porosity can be ensured by the core, while strength can be ensured by the shell.
[0054] The porosity of the shell can be lower than that of the core. For example... Figure 1 and Figure 2 As shown, the porous inorganic particles obtained according to this disclosure have many pores distributed in the core, thereby ensuring excellent bioactivity, and they have relatively fewer pores in the shell than in the core, or exhibit non-porousness in the absence of pores, thereby ensuring excellent strength.
[0055] This is believed to be because, in the spray drying process used to produce porous inorganic particles, second calcium-based particles with a maximum diameter of 1 μm to 10 μm constitute the core framework of the porous inorganic particles, and first calcium-based particles with a maximum diameter of 10 nm to 500 nm smaller than the maximum diameter of the second calcium-based particles move to the outside of the core framework of the porous inorganic particles to form a shell, such that the core is mostly composed of the second calcium-based particles and the shell is composed of both the second calcium-based particles and the first calcium-based particles.
[0056] Specifically, the porosity of the core can be 60% to 80%, and the porosity of the shell can be 0% to 60%. Porosity was analyzed using SEM images.
[0057] Meanwhile, 70% or more of all the first calcium-based particles may be contained in the shell. The porous inorganic particles include first calcium-based particles and second calcium-based particles, wherein 70% or more, or 80% or more, or 90% or more, or 100% or less, or 70% to 100% of, or 80% to 100% of, or 90% to 100% of the first calcium-based particles may be present in the shell.
[0058] The presence of 70% or more of all first calcium-based particles in the shell is defined as the presence of a majority of the first calcium-based particles in the shell, and specifically, 70% or more of all first calcium-based particles can be confirmed by measuring the volume of all first calcium-based particles.
[0059] The presence of a first calcium-based particle and a second calcium-based particle in a specified region is determined by the presence of either the first calcium-based particle or the second calcium-based particle in the specified region, and by excluding particles present at the boundary of the specific region.
[0060] Conversely, 30% or less, 20% or less, 10% or less, 0% or more, 0% to 30% or 0% to 20% or 0% to 10% of all second calcium-based particles may be present in the shell.
[0061] Simultaneously, 70% or more of all the second calcium-based particles may be contained in the core. The porous inorganic particles comprise a first calcium-based particle and a second calcium-based particle, wherein 70% or more, or 80% or more, or 90% or more, or 100% or less, or 70% to 100% of, or 80% to 100% of, or 90% to 100% of the second calcium-based particles may be present in the core.
[0062] The presence of 70% or more of the total volume of the second calcium-based particles in the nucleus is defined as the presence of the majority of the second calcium-based particles in the nucleus, and specifically, 70% or more of the total volume of the second calcium-based particles can be confirmed by measuring the volume of the total second calcium-based particles.
[0063] Conversely, 30% or less, 20% or less, 10% or less, 0% or more, 0% to 30% or 0% to 20% or 0% to 10% of all first calcium-based particles may be present in the nucleus.
[0064] The porous inorganic particles of the embodiment may include a shell comprising 70% or more of all first calcium-based particles and a core comprising 70% or more of all second calcium-based particles. As described above, in the porous inorganic particles, the second calcium-based particles may be predominantly distributed in the core, and the first calcium-based particles may be predominantly distributed in the shell.
[0065] Meanwhile, the porous inorganic particles may include the product of heat treatment of composite particles comprising a biocompatible binder, first calcium-based particles, and second calcium-based particles. By heat treating the composite particles comprising the biocompatible binder, first calcium-based particles, and second calcium-based particles, the biocompatible binder is removed through thermal decomposition, and fine pores are introduced into the interior of the calcium-based particles through partial sintering between the calcium-based particles. The content regarding the first and second calcium-based particles may include all of the above.
[0066] The weight-average molecular weight of biocompatible binders can range from 100,000 g / mol to 200,000 g / mol, or from 140,000 g / mol to 190,000 g / mol. In this specification, weight-average molecular weight refers to the weight-average molecular weight of the polystyrene as measured by GPC methods. In determining the weight-average molecular weight of the polystyrene as measured by GPC methods, commonly known analytical equipment, detectors such as refractive index detectors, and analytical columns can be used. Commonly applied temperature, solvent, and flow rate conditions can be used. Specifically, for example, measurements are performed using a Waters PL-GPC220 and a Polymer Laboratories PLgel MIX-B 300 mm length column. The evaluation temperature is 160 °C, 1,2,4-trichlorobenzene is used as the solvent, and the flow rate is 1 mL / min. A sample with a concentration of 10 mg / 10 mL is supplied in a 200 μL volume, and the Mw value is obtained using a calibration curve formed using polystyrene standards. Nine polystyrene standards with molecular weights of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000 were used.
[0067] Biocompatible adhesives may include one or more polymers selected from polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose, and polyethylene glycol. That is, biocompatible adhesives may include polymers that are polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose, polyethylene glycol, or mixtures thereof.
[0068] In a more specific example, a biocompatible binder could be polyvinyl alcohol (PVA). PVA has a boiling point of 228°C and can be removed while evaporating at 228°C or higher.
[0069] Therefore, the heat treatment of the composite particles may include subjecting them to a first heat treatment at a temperature of 450°C to 550°C and a second heat treatment at a temperature of 600°C to 1200°C. During the first heat treatment of the composite particles at a temperature of 450°C to 550°C or 480°C to 520°C, the biocompatible binder is evaporated and removed by thermal decomposition.
[0070] More specifically, in the first heat treatment, the temperature is raised to 450°C to 550°C or 480°C to 520°C at a heating rate of 2°C / min to 8°C / min or 4°C / min to 6°C / min, and then the heat treatment can be carried out at 450°C to 550°C or 480°C to 520°C for 1 hour to 3 hours.
[0071] Furthermore, during the second heat treatment process of subjecting the composite particles to a temperature of 600°C to 1200°C or 600°C to 1000°C, the composite particles containing pores and calcium-based particles are sintered, so that the sintered body of the calcium-based particles and porous inorganic particles including pores distributed in the sintered body can be formed.
[0072] If the sintering temperature is lowered excessively to below 600°C during the second heat treatment, it will be difficult to ensure sufficient strength of the sintered body. If the sintering temperature is raised excessively to above 1200°C, all the pores may be removed and non-porous inorganic particles may be formed.
[0073] More specifically, in the second heat treatment, the temperature can be raised to 600°C to 1200°C at a heating rate of 2°C / min to 8°C / min or 4°C / min to 6°C / min, and then the heat treatment can be carried out at 600°C to 1200°C for 1 hour to 3 hours.
[0074] Meanwhile, relative to 1 part by weight of the biocompatible binder, the content of calcium-based particles can be 30 parts by weight or more, or 40 parts by weight or more, or 50 parts by weight or more, or 100 parts by weight or less, or 90 parts by weight or less, or 80 parts by weight or less, or 70 parts by weight or less, or 60 parts by weight or less, or 30 to 100 parts by weight, or 40 to 100 parts by weight, or 50 to 100 parts by weight. Or 30 to 90 parts by weight, or 40 to 90 parts by weight, or 50 to 90 parts by weight, or 30 to 80 parts by weight, or 40 to 80 parts by weight, or 50 to 80 parts by weight, or 30 to 70 parts by weight, or 40 to 70 parts by weight, or 50 to 70 parts by weight, or 30 to 60 parts by weight, or 40 to 60 parts by weight, or 50 to 60 parts by weight.
[0075] At this point, the content of calcium-based particles refers to the total content of the first calcium-based particles and the second calcium-based particles.
[0076] If the content of calcium-based particles is excessively increased relative to 1 part by weight of biocompatible binder, almost no composite particles will form during spray drying due to the relatively reduced weight of the binder. On the other hand, if the content of calcium-based particles is excessively reduced relative to 1 part by weight of biocompatible binder, the composite particles after sintering will have low strength due to the relatively reduced weight of the calcium-based particles, making it difficult to maintain their shape and potentially causing the particle shape to become distorted.
[0077] More specifically, relative to 1 part by weight of the biocompatible binder, the content of the first calcium-based particles can be from 5 to 30 parts by weight, or from 5 to 20 parts by weight, or from 5 to 15 parts by weight. Furthermore, relative to 1 part by weight of the biocompatible binder, the content of the second calcium-based particles can be from 35 to 100 parts by weight, or from 35 to 50 parts by weight, or from 35 to 45 parts by weight.
[0078] Furthermore, relative to 1 part by weight of the first calcium-based particles, the content of the second calcium-based particles may be 2 to 10 parts by weight, or 2 to 5 parts by weight, or 3 to 10 parts by weight, or 3 to 5 parts by weight.
[0079] Meanwhile, the composite particles comprising a biocompatible binder, a first calcium-based particle, and a second calcium-based particle can be spray-dried products of a composition comprising a biocompatible binder, a first calcium-based particle, and a second calcium-based particle. Spray-dried products refer to products obtained by spray drying a composition comprising a biocompatible binder, a first calcium-based particle, and a second calcium-based particle. Spray drying offers rapid particle production speeds, eliminates the need for further drying steps for high productivity, does not use organic solvents, and is therefore produced using a safe spray drying method without explosion risks, thereby maximizing production efficiency.
[0080] Therefore, it can have significant advantages over the emulsion method, another production method that can be used for particle formation. This is because the limitation of the emulsion method is that it requires the further use of oil or organic solvents to form an emulsion, and it must be accompanied by washing and drying steps, which reduces productivity.
[0081] There are no particular restrictions on the shape of the composite particles, but spherical shapes are an example. There are no particular restrictions on the specific methods used to measure the shape of the composite particles, but they can be confirmed, for example, by SEM images.
[0082] The average maximum diameter of composite particles can range from 1 μm to 100 μm. The diameter of a composite particle is defined as the distance between two points where a straight line passing through the centroid of the particle intersects the particle's boundary line; the maximum value of these diameters corresponds to the maximum diameter. Furthermore, the value obtained by measuring the maximum diameter of multiple composite particles and calculating their arithmetic mean is called the average maximum diameter. There are no particular limitations on the specific methods used to measure the maximum diameter of composite particles, but examples can be confirmed, for instance, by using SEM images.
[0083] Composite particles can be a group of individual particles with an average maximum diameter of 1 μm to 100 μm, and the average maximum diameter of the individual particles included in the group can be 1 μm to 100 μm. More specifically, 95% or 99% of the individual particles included in the group can have a maximum diameter of 1 μm to 100 μm.
[0084] There are no particular limitations on the shape of porous inorganic particles, but spherical shapes are an example. There are no particular limitations on the specific methods used to measure the shape of porous inorganic particles, but it can be confirmed, for example, by SEM images. Because the porous inorganic particles meet the spherical shape requirement, they can be injected into the body with low injection force and elicit a low immune response in vivo.
[0085] Furthermore, the specific surface area of porous inorganic particles can be greater than 0.1 m². 2 / g, or 0.5m 2 / g or larger, or 1m 2 / g or larger, or 3m 2 / g or larger, or 4m 2 / g or larger, or 5m 2 / g or larger, or 10m 2 / g or less, or greater than 0.1m 2 / g and 10m 2 / g or less, or 0.5m 2 / g to 10m 2 / g, or 1m 2 / g to 10m 2 / g, or 3m 2 / g to 10m 2 / g, or 4m 2 / g to 10m 2 / g, or 5m 2 / g to 10m 2 / g. Specific surface area was measured using a BET analyzer. When the specific surface area of porous inorganic particles meets the above range, the porosity and specific surface area are higher than those of conventional high-density solid particles, thus improving bioactivity and achieving a rapid induction of the therapeutic effect of the filler. On the other hand, when the specific surface area of porous inorganic particles is excessively reduced to 0.1m... 2 When the porosity is / g or less, the porosity and specific surface area are as low as those of conventional high-density solid particles, and the bioactivity and therapeutic effect of the filler are reduced, which may lead to the problem of needing a large number of particles. In addition, if the specific surface area of porous inorganic particles is excessively increased, the strength of the inorganic particle sintered body will decrease, which may lead to the problem of limiting the available processes in the production of composite fillers.
[0086] Furthermore, the total pore volume of porous inorganic particles can be 0.001 cm³. 3 / g or greater, or 0.01cm 3 / g or greater, or 0.013cm 3 / g or greater, or 0.015cm 3 / g or greater, or 0.05cm 3 / g or less, or 0.001cm 3 / g to 0.05cm 3 / g, or 0.01cm 3 / g to 0.05cm 3 / g, or 0.013cm 3 / g to 0.05cm 3 / g, or 0.015cm 3 / g to 0.05cm 3 / g. Total pore volume refers to the total volume of all pores contained in porous inorganic particles, and is measured using a BET analyzer. When the total pore volume of porous inorganic particles meets the above range, the porosity and specific surface area are higher than those of conventional high-density solid particles, thus improving bioactivity and achieving the effect of rapidly inducing the therapeutic effect of the filler. On the other hand, when the total pore volume of porous inorganic particles is excessively reduced to less than 0.001 cm³, 3 At a density of / g, the porosity and specific surface area are as low as those of conventional high-density solid particles, resulting in reduced bioactivity and therapeutic efficacy of the filler, which may lead to the need for large quantities of particles. Furthermore, when the total pore volume of porous inorganic particles increases excessively, the strength of the sintered inorganic particle body decreases, which may limit the usable processes in the production of composite fillers.
[0087] Furthermore, the average maximum diameter of porous inorganic particles can be from 1 μm to 1000 μm, or 10 μm to 100 μm, or 10 μm to 45 μm, or 40 μm to 1000 μm, or 40 μm to 100 μm, or 40 μm to 45 μm. The diameter of a porous inorganic particle refers to the distance between two points where a straight line passing through the particle's centroid intersects the particle's boundary line, where the maximum value of these diameters corresponds to the maximum diameter. Additionally, the value obtained by measuring the maximum diameter of multiple porous inorganic particles and calculating their arithmetic mean is called the average maximum diameter. There are no particular limitations on the specific methods used to measure the maximum diameter of composite particles, but examples can be confirmed, for instance, by using SEM images.
[0088] Porous inorganic particles can be a group of individual particles having an average maximum diameter of 1 μm to 1000 μm, or 10 μm to 100 μm, or 10 μm to 45 μm, or 40 μm to 1000 μm, or 40 μm to 100 μm, or 40 μm to 45 μm, and the average maximum diameter of the individual particles included in the group can be 1 μm to 1000 μm, or 10 μm to 100 μm, or 10 μm to 45 μm, or 40 μm to 1000 μm, or 40 μm to 100 μm, or 40 μm to 45 μm. More specifically, the maximum diameter of 95% or 99% of the individual particles included in this group can be 1 μm to 1000 μm, or 10 μm to 100 μm, or 10 μm to 45 μm, or 40 μm to 1000 μm, or 40 μm to 100 μm, or 40 μm to 45 μm.
[0089] When the average maximum diameter of the porous inorganic particles meets the above range, the skin improvement effect can be maximized during treatment without in vivo side effects and pain. If the average maximum diameter of the porous inorganic particles decreases excessively to less than 1 μm, it may lead to excessive foreign body reactions in the body. On the other hand, if the average maximum diameter of the porous inorganic particles increases excessively to more than 1000 μm, not only will the specific surface area per particle mass decrease (which weakens the therapeutic effect), but it may also cause significant pain during treatment.
[0090] Meanwhile, the compressive strength of the porous inorganic particles is 20 MPa or greater, or 21 MPa or greater, or 22 MPa or greater, or 30 MPa or greater, or 35 MPa or greater, or 100 MPa or greater, or 70 MPa or greater, or 20 MPa to 100 MPa, or 21 MPa to 100 MPa, or 22 MPa to 100 MPa, or 30 MPa to 100 MPa, or 35 MPa to 100 MPa, or 20 MPa to 70 MPa, or 21 MPa to 70 MPa, or 22 MPa to 70 MPa, or 30 MPa to 70 MPa, or 35 MPa to 70 MPa.
[0091] Compressive strength is defined as the load per unit area when a porous inorganic particle breaks down by being subjected to compressive force in a single direction during a uniaxial compression test, and there are no particular limitations on the methods and apparatus used to measure it, and conventional methods for measuring the compressive strength of fine particles can be applied without limitation. In one instance, compressive strength can be measured using a micro-compression device.
[0092] When porous inorganic particles possess compressive strength within the above range, they can stably maintain their shape through high strength. On the other hand, if the compressive strength is excessively reduced to less than 20 MPa, the particle strength is low, making it difficult to maintain the shape and potentially causing the particle shape to become distorted.
[0093] 2. Composite fillers
[0094] According to another embodiment of this disclosure, a composite filler comprising porous inorganic particles of one embodiment and a biodegradable carrier can be provided.
[0095] The inventors have discovered through experiments that, in the case of a composite filler in another embodiment, which simultaneously contains porous inorganic particles and a biodegradable carrier from one embodiment, the stability of the biodegradable carrier and the bioactivity of the porous inorganic particles are combined to overcome the limitations of single-component fillers, while maintaining the initial volume. Then, through tissue stimulation by calcium particles, natural collagen is produced, thereby exhibiting the effect of improving the skin itself, and thus completing the present disclosure.
[0096] In particular, porous inorganic particles not only have higher porosity and specific surface area than existing high-density solid particles, and improved bioactivity to rapidly induce the therapeutic effect of fillers, but also have a rapid particle production rate, do not require further drying steps for high productivity, do not use organic solvents and are therefore produced by a safe spray drying method without explosion risk, thereby maximizing production efficiency.
[0097] Because the porous inorganic particles contained in the composite filler of another embodiment include a sintered body of calcium-based particles as described above and pores distributed within the sintered body, it has the effect of improving bioactivity and rapidly exhibiting skin-improving effects. The content regarding porous inorganic particles includes all of those described above in the embodiments.
[0098] Simultaneously, the composite filler may contain a biodegradable carrier. The biodegradable carrier serves as the substrate, matrix, or support of the composite filler, and the porous inorganic particles may be dispersed inside or outside the biodegradable carrier as described below.
[0099] There are no particular limitations on examples of biodegradable carriers, and a wide variety of biodegradable carriers widely used in the field of fillers can be used without restriction. Examples of biodegradable carriers include gelatin, hyaluronic acid (HA), carboxymethyl cellulose (CMC), chondroitin (sulfate / ester), dextran (sulfate / ester), chitosan, collagen, carboxymethyl chitin, fibroin, pullulan, polylactide, polyglycolic acid (PGA), polylactide-glycolic acid copolymer (PLGA), polyanhydride, polyorthoester, polyether ester, polycaprolactone, polyethylene glycol (PEG), cyclodextrin, poloxamer, or mixtures of two or more thereof.
[0100] Preferably, hyaluronic acid may be included as a biodegradable carrier. Hyaluronic acid is a naturally occurring biosynthesized substance abundant in the skin of animals, etc., and is hydrophilic due to its numerous hydroxyl groups (-OH), thus acting as a moisturizer in the skin of animals, etc. Hyaluronic acid is also present in human skin and has moisturizing effects, therefore it is frequently included in cosmetics. Hyaluronic acid reacts with the CD44 protein expressed in various epithelial cells to regulate a variety of physiological effects.
[0101] The composite filler may contain 1 to 50 parts by weight, 1 to 30 parts by weight, or 1 to 10 parts by weight of porous inorganic particles relative to 100 parts by weight of the biodegradable carrier. If the content of porous inorganic particles is excessively reduced relative to 100 parts by weight of the biodegradable carrier, skin improvement due to bioactivity may not occur. Furthermore, if the content of porous inorganic particles is excessively increased relative to 100 parts by weight of the biodegradable carrier, the porous inorganic particles in the composite filler may be unevenly dispersed, potentially leading to difficulties in successful injection into the body.
[0102] Meanwhile, according to Equation 1 below, the bioactivity of the composite filler can be 15 mg / (kg·g) or greater, or 16 mg / (kg·g) or greater, or 17 mg / (kg·g) or greater, or 18 mg / (kg·g) or greater, or 19 mg / (kg·g) or greater, or 100 mg / (kg·g) or less, or 15 mg / (kg·g) to 100 mg / (kg·g), or 16 mg / (kg·g) to 100 mg / (kg·g), or 17 mg / (kg·g) to 100 mg / (kg·g), or 18 mg / (kg·g) to 100 mg / (kg·g), or 19 mg / (kg·g) to 100 mg / (kg·g).
[0103] [Equation 1]
[0104] Bioactivity = {[content of ions (calcium or phosphorus ions) in body fluid (mg / kg)] - [content of ions (calcium or phosphorus ions) in body fluid after soaking the composite filler in body fluid for 8 days (mg / kg)]} / (content of inorganic particles in the composite filler (g)).
[0105] When the bioactivity of a composite filler meets the above range according to Equation 1, the filler has improved bioactivity, rapidly shows skin improvement effects, and is able to maintain initial volume and correction process.
[0106] At the same time, if the bioactivity is excessively reduced to less than 15 mg / (kg·g) according to Equation 1, there are disadvantages such as low bioactivity and slow skin improvement.
[0107] More specifically, according to Equation 2 below, the bioactivity of the composite filler can be 21 mg / (kg·g) or greater, or 22 mg / (kg·g) or greater, or 23 mg / (kg·g) or greater, or 25 mg / (kg·g) or greater, or 28 mg / (kg·g) or greater, or 29 mg / (kg·g) or greater, or 100 mg / (kg·g) or less, or 21 mg / (kg·g) to 100 mg / (kg·g), or 22 mg / (kg·g) to 100 mg / (kg·g), or 23 mg / (kg·g) to 100 mg / (kg·g), or 25 mg / (kg·g) to 100 mg / (kg·g), or 28 mg / (kg·g) to 100 mg / (kg·g), or 29 mg / (kg·g) to 100 mg / (kg·g).
[0108] [Equation 2]
[0109] Bioactivity = {[Calcium ion content in body fluid (mg / kg)] - [Calcium ion content in body fluid after soaking the composite filler in body fluid for 8 days (mg / kg)]} / (Inorganic particle content in the composite filler (g)).
[0110] Furthermore, according to Equation 3 below, the bioactivity of the composite filler can be 15 mg / (kg·g) or greater, or 16 mg / (kg·g) or greater, or 17 mg / (kg·g) or greater, or 18 mg / (kg·g) or greater, or 19 mg / (kg·g) or greater, or 21 mg / (kg·g) or greater, or 22 mg / (kg·g) or greater, or 100 mg / (kg·g) or less, or 15 mg / (kg·g) to 10 mg / (kg·g). 0 mg / (kg·g), or 16 mg / (kg·g) to 100 mg / (kg·g), or 17 mg / (kg·g) to 100 mg / (kg·g), or 18 mg / (kg·g) to 100 mg / (kg·g), or 19 mg / (kg·g) to 100 mg / (kg·g), or 21 mg / (kg·g) to 100 mg / (kg·g), or 22 mg / (kg·g) to 100 mg / (kg·g).
[0111] [Equation 3]
[0112] Bioactivity = {[Phosphorus ion content in body fluid (mg / kg)] - [Phosphorus ion content in body fluid after soaking the composite filler in body fluid for 8 days (mg / kg)]} / (Inorganic particle content in the composite filler (g)).
[0113] Additionally, if desired, the composite filler may also contain a variety of additive components typically included in fillers, such as lubricants like glycerin, phosphate buffers, etc.
[0114] 3. Products
[0115] According to another embodiment of this disclosure, a product comprising composite fillers from the other embodiments can be provided. The content regarding composite fillers includes all those described above in the other embodiments.
[0116] There are no particular restrictions on the types of products that can be used, and they can be applied without limitation depending on the purpose of the filler. Examples of products include food, pharmaceuticals, and cosmetics.
[0117] Beneficial effects
[0118] According to this disclosure, porous inorganic particles with high production efficiency and excellent bioactivity and strength can be provided, as well as composite fillers and products using them. Attached Figure Description
[0119] Figure 1 SEM images of the surface and cross-section of the porous inorganic particles obtained in Example 1 are shown.
[0120] Figure 2 SEM images of the surface and cross-section of the porous inorganic particles obtained in Example 2 are shown.
[0121] Figure 3 SEM images of the surface and cross-section of the porous inorganic particles obtained in Comparative Example 1 are shown.
[0122] Figure 4 SEM images of the surface and cross-section of the porous inorganic particles obtained in Comparative Example 2 are shown. Detailed Implementation
[0123] The invention will now be described in more detail with reference to the following embodiments. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of this disclosure.
[0124] <Example>
[0125] Example 1
[0126] (1) Production of porous inorganic particles
[0127] Polyvinyl alcohol (PVA, weight average molecular weight: 146,000 Da to 186,000 Da, 99+% hydrolyzed) was stirred in water at 90°C to prepare a 1% by weight PVA aqueous solution.
[0128] Spherical hydroxyapatite (HAp) powder with a maximum diameter of 200 nm (first HAp) and spherical hydroxyapatite (HAp) powder with a maximum diameter of 2.5 μm (second HAp) were added to a PVA aqueous solution to make the weight ratio of first HAp / second HAp / PVA satisfy 10 / 40 / 1 to prepare a suspension.
[0129] The suspension was spray-dried (Buchi mini spray dryer B-290). When drying was complete, granules were obtained, which were placed in a crucible and held in a box furnace at 500°C for 2 hours to remove PVA, and then sintered at 1000°C for 2 hours to produce porous inorganic granules.
[0130] (2) Production of composite fillers
[0131] 0.4g of porous inorganic particles were mixed with 9.6g of hyaluronic acid to produce a composite filler.
[0132] Example 2
[0133] Porous inorganic particles and composite fillers were produced in the same manner as in Example 1, except that the sintering temperature was changed to 1200°C, as shown in Table 1 below.
[0134] <Comparative Example>
[0135] Comparative Example 1
[0136] Porous inorganic particles and composite fillers were produced in the same manner as in Example 2, except that spherical hydroxyapatite (HAp) powder (second HAp) with a maximum diameter of 2.5 μm was added at a weight ratio of 0 / 50 / 1 for first HAp / second HAp / PVA instead of first HAp, as shown in Table 1 below.
[0137] Comparative Example 2
[0138] Porous inorganic particles and composite fillers were produced in the same manner as in Example 2, except that needle-shaped hydroxyapatite (HAp) powder (first HAp) with a maximum diameter of 150 nm was added at a weight ratio of 12 / 0 / 1 first HAp / second HAp / PVA instead of using second HAp, as shown in Table 1 below.
[0139] <Experimental Example>
[0140] The physical properties of the inorganic particles and composite fillers obtained in the examples and comparative examples were measured using the following methods, and the results are shown in Table 1, Table 2 and figures.
[0141] 1. Particle shape
[0142] The surface and cross-sectional shapes of the inorganic particles obtained in the examples and comparative examples were confirmed by SEM images, which are shown in the figures below. Figures 1 to 4 middle.
[0143] 2. Particle size
[0144] For the inorganic particles obtained in the examples and comparative examples, the maximum diameter of every 100 particles was measured by SEM images, and the arithmetic mean of these values was calculated.
[0145] 3. Porosity
[0146] For the inorganic particles obtained in the examples and comparative examples, the shape of the particle cross-section was confirmed by SEM images, and the porosity was expressed as follows based on the presence or absence of pores.
[0147] ○: Pores are present in the cross-sectional SEM image inside the particles.
[0148] X: No pores are present in the cross-sectional SEM image inside the particle.
[0149] 4. Specific surface area and total pore volume
[0150] The specific surface area and total pore volume of the inorganic particles obtained in the examples and comparative examples were measured using a BET analyzer.
[0151] 5. Particle strength
[0152] The compressive strength of the inorganic particles obtained in the examples and comparative examples was measured using a micro-compression device, and the compressive strength was evaluated as particle strength.
[0153] [Table 1]
[0154] Experimental measurement results of the examples and comparative examples
[0155]
[0156] As shown in Table 1, it was confirmed that when inorganic particles were included in the composite filler of the examples, porous inorganic particles with pores inside were obtained, and both the specific surface area and pore volume were significantly improved compared to Comparative Example 2. Furthermore, it was confirmed that when inorganic particles were included in the composite filler of the examples, the compressive strength of the porous inorganic particles was 22 MPa to 38 MPa, which was significantly improved compared to Comparative Example 1. On the other hand, it was confirmed that the compressive strength of the porous inorganic particles included in the composite filler of Comparative Example 1 was 15 MPa, which was lower than that of the examples. Furthermore, it was confirmed that when inorganic particles were included in the composite filler of Comparative Example 2, non-porous inorganic particles without pores inside were obtained.
[0157] 6. Bioactivity
[0158] After immersing the composite fillers obtained in the examples and comparative examples in simulated body fluid for 8 days, samples were prepared by acid digestion. The contents of Ca and P ions in the samples were measured using an ICP-OES apparatus (unit: mg / kg), and bioactivity was evaluated using Equation 1 below. The contents of Ca and P ions in the simulated body fluid were measured to be 42 mg / kg, which means that the higher the value of Equation 1 below, the better the bioactivity.
[0159] [Equation 1]
[0160] Bioactivity = {[content of ions (calcium or phosphorus ions) in body fluid (mg / kg)] - [content of ions (calcium or phosphorus ions) in body fluid after soaking the composite filler in body fluid for 8 days (mg / kg)]} / (content of inorganic particles in the composite filler (g)).
[0161] [Table 2]
[0162] Experimental measurement results of the examples and comparative examples
[0163] Example 1 29.2 22.2 Example 2 27.8 19.4 Comparative Example 1 27.8 20.8 Comparative Example 2 20.8 12.5
[0164] As shown in Table 2, it was confirmed that in the case of the composite filler of Example 1, the Ca ion bioactivity was 29.2 mg / (kg·g) and the P ion bioactivity was 22.2 mg / (kg·g), which were greater than the Ca ion bioactivity and P ion bioactivity of the comparative example, and therefore exhibited excellent bioactivity. On the other hand, the composite filler of Example 2 showed the same level of bioactivity as Comparative Example 1, and showed improved bioactivity compared to Comparative Example 2.
Claims
1. A porous inorganic particle, wherein the porous inorganic particle: It includes a sintered body composed of calcium-based particles and pores distributed within the sintered body, and A core-shell structure having a core with high porosity and a shell with lower porosity than the core. The calcium-based particles include first calcium-based particles with a maximum diameter of 10 nm to 500 nm and second calcium-based particles with a maximum diameter of 1 μm to 10 μm. The content of the second calcium-based particles is 2 to 10 parts by weight relative to 1 part by weight of the first calcium-based particles. Of which 70% or more by volume of all the first calcium-based particles are contained in the shell, Of which 70% or more by volume of all the second calcium-based particles are contained in the core, The porous inorganic particles include a product obtained by heat treatment of a composite particle comprising a biocompatible binder, the first calcium-based particle, and the second calcium-based particle. The heat treatment of the composite particles includes: The composite particles are subjected to a first heat treatment at a temperature of 450°C to 550°C for 1 to 3 hours, and the composite particles are subjected to a second heat treatment at a temperature of 600°C to 1200°C for 1 to 3 hours.
2. The porous inorganic particles according to claim 1, wherein: The porous inorganic particles have a core diameter of 20 μm to 90 μm and a shell thickness of 0.2 μm to 50 μm.
3. The porous inorganic particles according to claim 1, wherein: The ratio of the core diameter to the shell thickness of the porous inorganic particles is from 1:1 to 100:
1.
4. The porous inorganic particles according to claim 1, wherein: The total pore volume of the porous inorganic particles is 0.001 cm³. 3 / g or larger.
5. The porous inorganic particles according to claim 1, wherein: The porous inorganic particles have a specific surface area greater than 0.1 m². 2 / g.
6. The porous inorganic particles according to claim 1, wherein: The compressive strength of the porous inorganic particles is 20 MPa or greater.
7. The porous inorganic particles according to claim 1, wherein: The first calcium-based particle and the second calcium-based particle have a spherical shape.
8. The porous inorganic particles according to claim 1, wherein: The first calcium-based particle and the second calcium-based particle comprise hydroxyapatite.
9. The porous inorganic particles according to claim 1, wherein: The biocompatible adhesive includes one or more polymers selected from the following: polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose, and polyethylene glycol.
10. The porous inorganic particles according to claim 1, wherein: The content of the first calcium-based particles is from 5 to 30 parts by weight relative to 1 part by weight of the biocompatible binder.
11. The porous inorganic particles according to claim 1, wherein: The content of the second calcium-based particles is from 35 to 100 parts by weight relative to 1 part by weight of the biocompatible binder.
12. A composite filler comprising the porous inorganic particles according to claim 1 and a biodegradable carrier.
13. The composite filler according to claim 12, wherein: The biodegradable carrier includes hyaluronic acid.
14. A product comprising the composite filler according to claim 12.
Citation Information
Patent Citations
Red ginseng fermented product fermented with Bifidobacterium long gum and Lactobacillus paracasei and Method for preparing the same
KR1020220036793A
Degradable artificial bone particles with core-shell structure and preparation method thereof
CN111803715A